Dukungan Keluarga Terhadap Kualitas Hidup Pasien Hemodialisa di RS PKU Muhammadiyah Yogyakarta - Nur Chayati; Melinda Aria Ningsih (PENA NURSING, 2023)
Patients with chronic renal failure undergoing hemodialysis experience decreased kidney function to remove metabolic waste products in order to maintain fluid and electrolyte balance in the body. Various problems faced by patients are risk of reducing their quality of life. Support from family becomes one of the patient's sources of strength to survive. This study aims to determine the relationship between family support and quality of life of chronic kidney failure patients undergoing hemodialysis at PKU Muhammadiyah Hospital Yogyakarta. This study used a correlational research design with a cross sectional approach. Respondents amounted to 125 patients who were taken by total sampling technique. The results showed that the p-value = 0.000 or p <0.05 with a correlation coefficient (r) = 0.724, so it can be said that there is a very strong relationship between family support and the quality of life of chronic kidney failure patients undergoing hemodialysis at PKU Muhammadiyah Hospital Yogyakarta. From the results of the study, it can be concluded that family support is very strongly correlated with the quality of life of hemodialysis patients. The relationship of other variables such as age, gender, education, occupation, income, duration of hemodialysis, and frequency of hemodialysis on the quality of life of patients with chronic kidney failure requires analysis for further studies.